A high performance and low-cost hole transporting layer for efficient and stable perovskite solar cells - Mahmud, M.; Elumalai, Naveen Kumar; Upama, M.; Wang, D.; Gonçales, V.; Wright, M.; Xu, C.; Haque, F.; Uddin, A. (R S C Publications, 2017)
Here we report a small molecule oxidant 2,3,5,6-tetrafluoro-7,7,8,8-tetracyano-quinodimethane (F4TCNQ) doped, low cost 2′,7′-bis(bis(4-methoxyphenyl)amino)spiro[cyclopenta[2,1-b:3,4-b′]dithiophene-4,9′-fluorene] (FDT) hole transporting layer (HTL) for efficient mixed organic cation based MA0.6FA0.4PbI3 (MA = methyl ammonium, FA = formamidinium) perovskite solar cells (PSCs), fabricated via a highly reproducible controlled nucleation assisted restricted volume solvent annealing method, having full temperature compatibility with flexible substrates. The optimized (1 wt%) F4TCNQ doped FDT HTL based devices (F-FDT devices) demonstrate simultaneous enhancement of photovoltaic performance and device stability as well as significant reduction in photo-current hysteresis, as compared to conventional bis(trifluoromethylsulfonyl)amine lithium (Li-TFSI) additive based FDT HTL devices (L-FDT devices). Adding to the merits, F-FDT PSCs exhibit about 75% higher device stability compared to conventional L-FDT devices during the course of three weeks. Mott–Schottky analysis and in-depth charge transport characterization were carried out using electrochemical impedance spectroscopy (EIS) of the fabricated devices to understand the superior performance of the F-FDT devices. In addition, detailed polaronic intensity characterization of the doped HTL films was performed via ultraviolet-visible near-infrared (UV-vis-NIR) spectroscopy to investigate the underlying mechanism. Mitigated photocurrent hysteresis in the F-FDT devices has also been examined in terms of the inherent electrode polarization phenomenon. Furthermore, the superior device stability of the F-FDT PSCs has been probed in terms of variation in electronic properties, surface wettability, crystallinity, and microstrain dislocation density, and a detailed picture of the underlying mechanism behind stability enhancement is presented.